PENERAPAN METODE PEMBELAJARAN PBL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KARAKTER DEMOKRASI DALAM PEMBELAJARAN PENDIDIKAN PANCASILA PADA SISWA KELAS XI DI SMA NEGERI 3 SALATIGA - Karmaham, Agusto; Mediatati, Nani (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
This study aims to describe the application of the Problem-Based Learning (PBL) method in improving students' critical thinking skills and democratic character in Pancasila Education. The research used the Classroom Action Research (CAR) method, which was carried out in two cycles, each consisting of two meetings. The research subjects were 35 students of class XI.2 at State Senior High School 3 Salatiga in the 2025/2026 academic year. Data collection techniques used observation and tests. The results showed that the application of the PBL method could improve students' critical thinking skills, as indicated by an increase in the average score from 57.3 (low category) in the pre-cycle to 70.1 (medium category) in cycle I, and further increased to 80.3 (high category) in cycle II. Students' democratic character also improved from an average of 55.71% (low category) in the pre-cycle to 74.75% (medium category) in cycle I, and increased to 87.61% (high category) in cycle II. The PBL method can be used as an alternative learning strategy to develop 21st-century skills and democratic values in students. Simultaneous measurement of two variables in the context of Pancasila Education at the senior high school level.   Keywords: Problem-Based Learning; Critical Thinking; Democratic Character, Pancasila Education.